ADAR1 suppression causes interferon signaling and transposable element transcript accumulation in human astrocytes - McEntee, Cali M.; Cavalier, Alyssa N.; LaRocca, Thomas J. (Frontiers in Molecular Neuroscience, 2023)
Neuroinflammation is a central mechanism of brain aging and Alzheimer’s disease (AD), but the exact causes of age- and AD-related neuroinflammation are incompletely understood. One potential modulator of neuroinflammation is the enzyme adenosine deaminase acting on RNA 1 (ADAR1), which regulates the accumulation of endogenous double-stranded RNA (dsRNA), a pro-inflammatory/innate immune activator. However, the role of ADAR1 and its transcriptomic targets in astrocytes, key mediators of neuroinflammation, have not been comprehensively investigated. Here, we knock down ADAR1 in primary human astrocytes via siRNA transfection and use transcriptomics (RNA-seq) to show that this results in: 1) increased expression of type I interferon and pro-inflammatory signaling pathways; and 2) an accumulation of transposable element (TE) transcripts with the potential to form dsRNA. We also show that our findings may be clinically relevant, as ADAR1 gene expression declines with brain aging and AD in humans, and this is associated with a similar increase in TE transcripts. Together, our results suggest an important role for ADAR1 in preventing pro-inflammatory activation of astrocytes in response to endogenous dsRNA with aging and AD.